FIBER WASTE CLEANING - Ulugbek Muminov; Guzalkhan Muminova (Journals Park Publishing, 2024)
This article highlights that only OVM-type cleaners have been produced for cleaning fibrous waste, and there has been insufficient scientific research aimed at improving these cleaners.
Keywords: Fiber, cotton cultivation, lintering, raw materials, OVP.